Overall performance of domestic gas meter operations - Mohsin, R. (Faculty of Chemical and Natural Resource Engineering, UTM, 2008)
In the current era of technology and its applications, the usage of gas in industries and daily activities is on the rise. Under the PGU scheme, the demand for Methane or sales gas raised ten folds from about 100 million standard cubic feet per day (MMscfd) in 1984 to approximately 1,000 MMscfd in 1995. The gas distribution mix of 65 percent or 1,300 MMscfd was reserved for electricity generation, 8 percent for export market (Singapore) and the remaining 27 percent was for industrial, commercial and resident consumers as well as for use feedstock by petrochemical industries. The Malaysia Government's fourfuel diversification policy aimed at reducing the country's dependence on oil as an energy source and the emphasis towards the usage of a more efficient and cleaner burning fuel also give a momentum to increase the usage of natural gas [1]. In line with this, Malaysia has attained and thus practicing the knowledge of gas transmission and distribution. The metering process is something that can be foreseen because of its dauntless importance in the gas industry. As much as the importance of metering, the accuracy of each and every meter is very important. Based on the specification and standards, a series of mechanical contrivances such as valves, regulators, detectors and meters are placed accordingly as to attain the best result in the calibration. At present, the increasing number of gas domestic customer either employing Natural Gas (NG) or Liquefied Petroleum Gas (LPG) as their burning fuel has driven attention towards accuracy of gas transfer. Losses to custodian may have significant impact in terms of monetary returns[2]. This type of losses may be directly related to the' effect of measurement accuracy and pressure losses. Therefore there is a need to study the overall performance in low flowrate gas system in the domestic sector. By the development of a scale model flow system using domestic gas meters, the pressure losses performance and other factors such as flow rate, compositional effect of test fluid can be monitored carefully and could lead to the formulation and understanding of the pressure capacity and its consequence effect to the metering accuracy. This is also in line with SIRI initiative to establish standards in the domestic gas meter applications.